The Impact of a Large Parental Leave Benefit Reform on the Timing of Birth around the Day of Implementation - Marcus Tamm (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2009)
The introduction of the German parental leave benefit (Elterngeld) applied to all children born on January 1st, 2007 or later. The new Elterngeld considerably changed the amount of transfers to families during the first two years postpartum. We show that the incentives created by using a cut-off date led more than 1000 parents to postpone the delivery of their children from December 2006 to January 2007. Besides analyzing the timing of delivery the paper focuses on potential adverse health outcomes of children affected by the shift in date of birth.
Keywords: H31; J13; 330; Cut-off date effect; fertility; policy evaluation; Erziehungsurlaub; Sozialreform; Wirtschaftspolitische Wirkungsanalyse; Fruchtbarkeit; Deutschland